Growth and Characterization of M-Plane GaN on \(γ\)-LiAlO2 (100) Substrates by Plasma-Assisted Molecular Beam Epitaxy - Yu-Chiao Lin; Ikai Lo; Hui-Chun Shih; Mitch M. C. Chou; D. M. Schaadt (New Frontiers in Physical Science Research Vol. 5, 2022)
On LiAlO2 substrates, M-plane GaN thin films were produced using plasma-assisted molecular beam epitaxy at various N/Ga flux ratios. As the N/Ga flux ratio decreased, the GaN surface trended to a flat morphology with stripes along [11\(2\)0] and exhibited a better crystal quality. This trend had been investigated that the substrate could be damaged by N2 plasma during the high N/Ga flux ratio growth condition and easily cause the formation of Li5GaO4 on the interface between GaN and substrate.